1963
DOI: 10.1111/j.1151-2916.1963.tb11738.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Orientation on Plastic Deformation of Magnesium Oxide

Abstract: Stress-strain data for single crystals of MgO tested in compression with (110) and (11 1) loading axes are presented for temperatures ranging from 26' to 125OOC. Stress-strain data for polycrystalline MgO are also presented over the same temperature range. Single crystals with a (111) loading axis were found to deform plastically on the {loo) (110) slip systems at temperatures above 35OOC. The total strain at fracture for polycrystalline MgO at room temperature was about 0.6%; above 600'C it was about 2%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

1967
1967
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 6 publications
2
35
1
Order By: Relevance
“…They are referenced in Table 1. In the study of Hulse and collaborators, the authors showed that CRSS are larger in 1 ⁄2<110>{100} than in 1 ⁄2<110>{110} slip systems for temperatures ranging from 300 K to 1500 K [5]. This study emphasizes that only four out of six 1 ⁄2<110>{110} slip systems are effective under <100> and <110> compression, with Schmid factors of about 0.5 and 0.25, respectively.…”
Section: Lattice Dislocations and Slip Systems In Mgomentioning
confidence: 93%
See 4 more Smart Citations
“…They are referenced in Table 1. In the study of Hulse and collaborators, the authors showed that CRSS are larger in 1 ⁄2<110>{100} than in 1 ⁄2<110>{110} slip systems for temperatures ranging from 300 K to 1500 K [5]. This study emphasizes that only four out of six 1 ⁄2<110>{110} slip systems are effective under <100> and <110> compression, with Schmid factors of about 0.5 and 0.25, respectively.…”
Section: Lattice Dislocations and Slip Systems In Mgomentioning
confidence: 93%
“…Several additional studies addressed the effect of temperature on the CRSS for the 1 ⁄2<110>{110} slip systems [18][19][20][21][22] while only few datasets focus on 1 ⁄2<110>{100} [5,8,22]. These data are shown in Figure 2.…”
Section: Critical Resolved Shear Stress (Crss)mentioning
confidence: 94%
See 3 more Smart Citations